Utilization of Iron Ore Slag in The Manufacture of Calcium Silicate Boards - Hendronursito, Yusup; Amin, Muhammad; Al Muttaqii, Muhammad; Karo Karo, Pulung; Yulia, Andini; Candra Birawidha, David; Isnugroho, Kusno (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
This study aims to determine the iron ore slag effect as an additive in particleboard based on the SNI 7705:2011 standard. Iron ore slag comes from the waste processing of iron ore into sponge iron. The iron ore slag is reduced to a size of 200 mesh. Particleboard made with the composition of slag and silica is 0:40, 8:32, 16:24, 20:20, 24:16, 32:8, and 40:0 wt%. Meanwhile, other materials were made permanent, namely PCC cement and lime 16 wt%, coconut fiber 3wt%, and water 3 wt%. They are pressed with 3 tons of pressure for 1 hour using a hydraulic press. Drying at room temperature for one day, under the hot sun for two days, then in an oven at 110 oC for 8 hrs. Analysis of the chemical composition of X-ray fluorescence and X-ray diffraction crystalline phase, SEM-EDS micro-photographs, physical tests including density and porosity, and mechanical compressive strength tests. The dominant composition of SiO2 and CaO affects the formation of silicon dioxide (SiO2), calcium silicate (CaSiO3), and dicalcium silicate (Ca2SiO4) phases. Silica has a positive effect on the compressive strength of particleboard but is different from Ca, which has an impact on reducing the compressive strength. The sem morphology shows that coconut fiber cannot withstand heating at 190 oC and results in agglomeration. The addition of 20% ore slag and silica has met the calcium silicate board SNI 7705-2011. These results can be used to develop slag waste from iron ore processing into much more useful objects.